“Desprotección de los Derechos: a ser Escuchados, Igualdad, y a la Identidad de las Niñas, Niños y Adolescentes que se encuentran Condición de Migrante”. - Gutama Castro, Daysi Fernanda (2024)
This research work is titled “Lack of protection of the right of adolescents' parents to be heard, to equal rights and to their children's identity when they are in a migrant situation”, Considering the refusal of the Civil Registry authority to register the children of adolescent migrants mothers without legal representation in the country, the interest in developing the research stems from the lack of legal representation in the country by the Children of Adolescent Migrant Mothers. Specifically, the Civil Registry has stated that its employees are acting in accordance with Article 24 of the Organic Law on Identity and Civil Data Management. In addition to the requirements established in the law and these regulations, a minor parent who registers or recognizes a child must be accompanied by his or her legal representative. An essential provision of article 7 of the Convention on the Rights of the Child is that a child is to be registered immediately following his or her birth and has the right to a name, to acquire a nationality, and, as far as possible, to know and be cared for by their parents. This study also demonstrates that a series of constitutional rights are violated, such as the rights of children to identity, legal personality, registration and registration of birth, the right to nationality, as well as the rights of adolescent migrant parents to equality and non-discrimination of their rights, protection of the right of the family, and to be heard and to have their opinion seriously considered. Since adolescent migrant parents cannot count on a legal representative to guarantee the birth registration of their children due to different situations, they have been forced to resort to institutions such as the Ombudsman's Office and the Public Defender's Office. To ensure that adolescents and their children are registered for birth, these institutions have initiated and activated processes of jurisdictional guarantees. This work was developed using materials and methods that enabled the development of the same, which included the development of surveys and interviews with legal professionals. The results of the study were helpful in proposing pro-active guidelines for ensuring the fulfillment of the rights of migrant adolescent parents and their children, rights that are being violated by the Civil Registry authority.